190k views
2 votes
Make a the subject of this formula:
p=n^2+a/n+a

User Journeyman
by
6.5k points

1 Answer

1 vote

Explanation:

we multiply both sides by the denominator on the right to eliminate fraction, so we have..

p*(n+a)= (n²+a/n+a)*n+a

so we have

p(n+a)= n²+a

so opening the bracket on the left hand side we have,

p*n+p*a

pn+pa

so,

pn+pa= n²+a

so collecting like terms we have,

pn-n²= a-pa

so removing a from the equation on the right hand side we have,

pn-n²=a(1-p)

dividing both sides by the equation in the bracket on the right hand side, we have..

pn-n²/(1-p)= a

a = pn-n²/1-p

or

a = n(p-n)/1-p

User Hasan Fathi
by
6.7k points